Pengaruh Program Tayangan Sepak Bola BRI Liga 1 Indonesia di Stasiun Televisi Indosiar terhadap Minat Menonton Televisi bagi Remaja: Survei pada Mahasiswa Ilmu Komunikasi FISIP UMJ Angkatan 2020 dan 2021 - Zaidan Arigi Maulidhika; Donny Kurniawan (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
Television programming encompasses the various shows broadcast on TV, including news, sports, drama, comedy, documentaries, and reality shows. These programs aim to inform, entertain, and educate viewers. This study focuses on the BRI Liga 1 Indonesia soccer program aired on Indosiar, examining its influence on television viewing interest among adolescents, specifically Communication Studies students at the University of Muhammadiyah Jakarta, Class of 2020/2021. The research employs program theory aspects, including conflict, duration, and trends, along with theories of cognitive, affective, and conative viewing interest. Using a quantitative approach, the study distributes questionnaires to 78 respondents through random sampling. The findings reveal that the BRI Liga 1 program has a 70.5% impact on viewing interest, while 29.5% is attributed to other factors. Hypothesis testing shows that t_count (13.509) exceeds t_table (1.665), leading to the rejection of H0 and acceptance of H1. This confirms that the BRI Liga 1 Indonesia soccer program significantly influences television viewing interest among adolescents.